Bussiness Model Canvas: Drying Rack Pulley System / Siti Nabilah Ruslin - Ruslin, Siti Nabilah (2020)
Drying rack or clotheshorse is a frame upon which clean wet laundry is hung to dry by evaporation. The frame is usually made of wood, metal or plastic. It is a cheap low-tech piece of laundry equipment, as opposed to a clothes dryer, which necessitates electricity. There are a few names for this device including clothes rack, drying horse, clothes maiden, garment donkey, drying rack, scissor rack, drying stand, clotheshoose Frostick, airer, or (Scots) Winter Dyke. A drying rack and clothes lines serve the same purpose drying clothes that have been recently washed, or that are wet in general. and used as an alternative to the powered clothes dryer. A drying rack or clotheshorse can help save space in an apartment, or clothes lines can be strung in the basement during the winter. Small loads can simply be draped over furniture or a shower curtain pole. The drying time indoors will typically be longer than outdoor drying because of the lack of direct solar radiation and the convective assistance of the wind. The evaporation of the moisture from the clothes will cool the indoor air and increase the humidity level, which may or may not be desirable. In cold, dry weather, moderate increases in humidity make most people feel more comfortable. In warm weather, increased humidity makes most people feel even hotter. Increased humidity can also increase growth of fungi, which can cause health problems